2017
DOI: 10.1038/s41598-017-14257-4
|View full text |Cite
|
Sign up to set email alerts
|

From receptor binding kinetics to signal transduction; a missing link in predicting in vivo drug-action

Abstract: An important question in drug discovery is how to overcome the significant challenge of high drug attrition rates due to lack of efficacy and safety. A missing link in the understanding of determinants for drug efficacy is the relation between drug-target binding kinetics and signal transduction, particularly in the physiological context of (multiple) endogenous ligands. We hypothesized that the kinetic binding parameters of both drug and endogenous ligand play a crucial role in determining cellular responses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…For NK 1 R, the kinetic characterization of the endogenous ligands led to an excellent correlation between the ligand’s RT and in vitro efficacy, as well as between the ligand’s k on and the in vitro potency, as determined via a label-free assay . Moreover, a follow-up study showed that antagonists display different inhibitory potencies depending on the binding kinetics of the endogenous agonist …”
Section: Ligand Variants Affecting Ligand–receptor Binding Kineticsmentioning
confidence: 96%
See 2 more Smart Citations
“…For NK 1 R, the kinetic characterization of the endogenous ligands led to an excellent correlation between the ligand’s RT and in vitro efficacy, as well as between the ligand’s k on and the in vitro potency, as determined via a label-free assay . Moreover, a follow-up study showed that antagonists display different inhibitory potencies depending on the binding kinetics of the endogenous agonist …”
Section: Ligand Variants Affecting Ligand–receptor Binding Kineticsmentioning
confidence: 96%
“…87 Moreover, a follow-up study showed that antagonists display different inhibitory potencies depending on the binding kinetics of the endogenous agonist. 23 In case of the GnRHR, synthetic GnRH analogs displayed RTs ranging from 6 to 111 min in radioligand binding assays, whereas the RT measured by time-resolved fluorescence resonance energy transfer (FRET) varied from 2 to 61 min. 30 Interestingly, the RT of GnRH itself was around 6 min, indicating that most of these synthetic analogs had a longer RT.…”
Section: Motulsky−mahan Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from fine structural studies revealing activated and inactivated conformations of the receptors induced by movements of receptor domains, determining the binding kinetics of both agonist and antagonist ligands deserves attention to ascertain signal transduction outcomes and determine new drugs' specificity, efficacy, modulation, and potency [117].…”
Section: Nk-1r Signaling Pathwaysmentioning
confidence: 99%
“…In contrast to binding assays that are routinely performed with cell homogenates or isolated membranes, functional assays are performed on intact living cells and, consequently also account for dynamic cellular processes such as effector pre-coupling, receptor reserve and receptor regulation. Fast and/or real time cellular responses such as Ca 2+ influx, cyclic adenosine-monophosphate (cAMP) production and cellular impedance-based assays, have recently been used to measure the recovery of receptor responsiveness as measure of pre-bound antagonist dissociation upon washout of unbound antagonist [3,7,9,10,11,12]. Indeed, recovery time of Gα q -coupled histamine H 1 receptor (H 1 R) responsiveness in a Ca 2+ mobilization and label free dynamic mass redistribution (DMR) assay after antagonist washout highly correlated to residence times of these antihistamines, as determined in competitive radioligand binding assays [7].…”
Section: Introductionmentioning
confidence: 99%